Illness-Promoting Psychological Processes in Children and Adolescents with Functional Neurological Disorder - Kasia Kozlowska; Olivia Schollar-Root; Blanche Savage; Clare Hawkes; Catherine Chudleigh; Jyoti Raghunandan; Stephen Scher; Helene Helgeland (MDPI AG, 2023)
Previous studies suggest that subjective distress in children with functional neurological disorder (FND) is associated with stress-system dysregulation and modulates aberrant changes in neural networks. The current study documents illness-promoting psychological processes in 76 children with FND (60 girls and 16 boys, aged 10.00−17.08 years) admitted to the Mind-Body Program. The children completed a comprehensive family assessment and self-report measures, and they worked with the clinical team to identify psychological processes during their inpatient admission. A total of 47 healthy controls (35 girls and 12 boys, aged 8.58-17.92 years) also completed self-report measures, but were not assessed for illness-promoting psychological processes. Children with FND (vs. controls) reported higher levels of subjective distress (total DASS score, t(104.24) = 12.18; p ˂ 0.001) and more adverse childhood experiences across their lifespans (total ELSQ score, t(88.57) = 9.38; p ˂ 0.001). Illness-promoting psychological processes were identified in all children with FND. Most common were the following: chronic worries about schoolwork, friendships, or parental wellbeing (n = 64; 84.2%); attention to symptoms (n = 61; 80.3%); feeling sad (n = 58; 76.3%); experiencing a low sense of control (helplessness) in relation to symptoms (n = 44; 57.9%); pushing difficult thoughts out of mind (n = 44; 57.9%); self-critical rumination (n = 42; 55.3%); negative/catastrophic-symptom expectations (n = 40; 52.6%); avoidance of activities (n = 38; 50%); intrusive thoughts/feelings/memories associated with adverse events (n = 38, 50%); and pushing difficult feelings out of mind (n = 37; 48.7%). In children with FND-disabled enough to be admitted for inpatient treatment-illness-promoting psychological processes are part of the clinical presentation. They contribute to the child's ongoing sense of subjective distress, and if not addressed can maintain the illness process. A range of clinical interventions used to address illness-promoting psychological processes are discussed, along with illustrative vignettes.